(3GdCSGei hGdcfis - (3GdMGce GdcHjQ , eMeO Hf eMeO Hf CMeO Hf ESMGb GdcQGHjS, CHh CMeO,J (B378 (3g` s ((3GdMGaX GdefPQi s)
(3ChdgG (B:s
(3CHh YHO Gddg eMeO Hf YHO Gddg Hf GSMGb GdWhSi SeY CfG eUYH CMeO Hf CHj HcQ GdRgQi s
(3BNQgG (B:s
(3bGd QaGYI GdfMdi SdjeGf bGd GdfHi Udi Gddg Ydjg hSde GPG efJ adG JbJdg s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B182 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B50s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B11 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs